DEACTIVATION OF PALLADIUM CATALYST SUPPORTED BY ALUMINA IN THE PRODUCTION OF GLYPHOSATE - Edia Rahayuningsih; I Made Bendiyasa; Nuryono Nuryono; Jupiter Jupiter (ASEAN Journal of Chemical Engineering, 2011)
During the production process of glyphosate from n-phosponomethyl iminodiacetic acid (NPMIDA) and hydrogen peroxide (H2O2 Five grams of NPMIDA, 0.3 grams of fresh palladium catalyst, and 85 mL of H), deactivation of the catalyst used may occur, which will decrease the production of glyphosate. To controll the rate of production the deactivation process of the catalyst needs to be evaluated. 2O were put into a three neck flask. One mL of H2O2 was added into the mixture every ten minutes, so that the total amount of H2O2 The activity as a function of temperature and time can be expressed as follows: added was 9 mL. The reaction was kept going for another 15 minutes. The catalyst was filtered and its filtrate collected in a 500 mL erlenmeyer glass. The filtrate was then naturally cooled to room temperature and 130 mL of technical grade ethanol was added to it. The solution was left overnight for the crystal formation. The glyphosate crystal formed was then separated from the solution and washed with 40 mL of technical grade ethanol, followed by 40 mL of technical grade ether. Finally the glyphosate crystal was dried in open air. The amount of crystal glyphosate produced was weighed and its purity was analyzed using UV/Vis spectrophotometer. The catalyst was then reused in the next experiments using the same procedure.The activity as a function of temperature and time can be expressed as follows:φ(T,t) = α t(-n)where α = 0.027T - 7.99 and (-n) = 0.005T + 1.62. These parameters hold for temperatures (T) of 333K to 363K. At 363K, the rate of deactivation of the catalyst is the fastest. Experiments that were run at 348K resulted in higher glyphosate productivity compared to other temperatures.